Мост в чужую мечту: роман / Дмитрий Емец - Емец Дмитрий Александрович (Школа ныряльщиков, 2012)
Экземпляры: С/а ДБ (20131111) / Инвентарный номер: 100280 / Цена: 197.60 / Авт.знак: Е 60 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6